2008
DOI: 10.1111/j.1744-7402.2008.02236.x
|View full text |Cite
|
Sign up to set email alerts
|

Porous Si/SiC Composite Based on Nonwoven Cellulosic Fabrics: Synthesis and Characterization

Abstract: The microstructure and properties of porous Si/silicon carbide (SiC) composites manufactured from nonwoven cellulosic fabrics have been investigated. A fibrillar reaction product with a microstructure reproducing the initial preform morphology consisting of b-SiC and unreacted Si was obtained. Improvement of strength is expected to be achieved by increase of SiC content and reduction of porosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Multiphysical porous media thermofluid dynamics continues to attract the attention of the applied mathematics and engineering science research communities owing to ever‐increasing applications in many branches of chemical and mechanical engineering. Both Newtonian and non‐Newtonian heat and momentum transfer (and mass transfer) in conducting or nonconducting saturated porous regimes constitute many of the fundamental flows encountered in for example silcion/silicon carbide porous media composite synthesis, pyrolytic reactive sintering processes in the high‐temperature production of uniformly porous composites, foam manufacture and treatment, aerosol expropriation from organic systems, evaporation and drying capillary porous material systems, chemical vapor deposition within porous substrate media for the preparation of reinforced ceramic‐matrix composites, electro‐osmotic porous media flow control methods such as electrokinetic soil remediation with cathode rinsing, and combustion processes in porous regimes for use in auto‐ignition systems . The consensus in many studies has been to employ the well‐validated Darcy law for porous media simulation, which retains validity for low Reynolds number, viscous‐dominated flows.…”
Section: Introductionmentioning
confidence: 99%
“…Multiphysical porous media thermofluid dynamics continues to attract the attention of the applied mathematics and engineering science research communities owing to ever‐increasing applications in many branches of chemical and mechanical engineering. Both Newtonian and non‐Newtonian heat and momentum transfer (and mass transfer) in conducting or nonconducting saturated porous regimes constitute many of the fundamental flows encountered in for example silcion/silicon carbide porous media composite synthesis, pyrolytic reactive sintering processes in the high‐temperature production of uniformly porous composites, foam manufacture and treatment, aerosol expropriation from organic systems, evaporation and drying capillary porous material systems, chemical vapor deposition within porous substrate media for the preparation of reinforced ceramic‐matrix composites, electro‐osmotic porous media flow control methods such as electrokinetic soil remediation with cathode rinsing, and combustion processes in porous regimes for use in auto‐ignition systems . The consensus in many studies has been to employ the well‐validated Darcy law for porous media simulation, which retains validity for low Reynolds number, viscous‐dominated flows.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the formation of WC single phase by carbothermal reduction proceeds through reduction of WO 3 to W via the formation of lower oxides of tungsten, followed by carburization into WC. WC is directly formed without forming W 2 C. On the other hand, synthesis of SiC structures by mimicking the cellular tissue anatomy of natural biostructures such as rice husks, wood tissue, wood fibers and papers has attracted much interest (22)(23)(24)(25)(26) . Cellular materials offer unique properties (27) such as: good specific stuffiness and strength and high energy absorption under impact.…”
Section: Introductionmentioning
confidence: 99%